(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The use of imagery-associative mnemonic techniques is increasingly recognized as a powerful tool for accelerating the processing of oral text during simultaneous interpretation. This approach, rooted deeply in cognitive psychology and linguistic studies, capitalizes on the brain’s inherent capacity to remember and reconstruct information through visual and associative connections. In the fast-paced environment of simultaneous translation, where interpreters are required to comprehend, transfer, and reproduce meaning in real time, such techniques serve as a critical bridge between comprehension and production. The following essay thoroughly discusses the theory and practical significance of imagery-associative mnemonics in the context of simultaneous interpretation, as well as how their systematic application contributes to cognitive flexibility, memory retention, and efficiency in interpreting oral texts.